PENGARUH INTENSITAS CAHAYA LAMPU PERANGKAP TERHADAP POPULASI DAN INTENSITAS SERANGAN PENGGEREK BATANG PADI PUTIH Scirpophaga innotata wlk. (Lepidoptera:Pyralidae) PADA TANAMAN PADI - Larioh, Novita Kristina; Toana, Moh Hibban; Pasaru, Flora (AGROTEKBIS, 2018)
This study aimed to know the effect of light trap intensity on the population density and intensity of S. Innotata attack. This research was conducted using the method of observation, with two light trap type of LED with a power of 5 watts and 10 watts, each light trap placed between two observed plots. Observation plots were observed in this study were four plots with the size of 30x20,5m. In each sectional observation was made by 5 measuring of 2x2m observation point, so that the total number of observed in plots this study were 20 subplots. Planting on each plot using âJajar Legowoâ system with the size of 20x40m. Population and intensity of S. innotata were analyzed using t-test. The results of this study showed that the number of adult S. innotata at 5 watt lamp light treatments da 10 watt increased starting from the first week of observation until the final week of observation, where the observation is done once a week for 8 times observation. Total catches imago of S. innotata at most in 5 watt is 110 tails and in 10 watts the highest number of catches is 219 and the result of t-test analysis is that the treatment between the fluorescent lights of 5 watts and 10 watts significantly effect on the intensity of S. innotata observed.Â Keywords: Intensity of the attack, Lamps traps, and S.innotata, population.